Pushing the edge in narrative inquiry. (November 2021) - Barkhuizen, Gary; Consoli, Sal
Abstract: This article introduces a Special-topic Issue that revisits methodology in narrative inquiry. In particular, the authors present a reflexive discussion of their respective theoretical and empirical engagement with narrative research and highlight a series of issues which are critical to the execution of rigorous and systematic narrative inquiry. Significantly, the article offers a review of the contributions to this SI within a framework of 'core dimensions' of narrative inquiry (Barkhuizen, 2019). Further, it offers an innovative and fresh perspective on the key methods used within the flourishing tradition of narrative inquiry in language learning and teaching. The authors raise timely questions about the status quo and innovation in narrative research, including those to do with the concept of 'story', researcher engagement, researcher positionality, the messy nature of data gathering and data analysis, as well as the complexities of (re)presenting narrative findings. Ultimately, this article encourages a culture of methodological investment in narrative inquiry which, through creative, reflexive and ethical considerations, pushes the edge of what we know and do as narrative researchers in language teaching and learning.